Humanitarian Calls For Blood Donation: Construction of Binary Message on @pmikotabogor - Koesworo Setiawan (Jurnal Bahasa dan Sastra, 2023)
The blood stock of the Indonesian Red Cross (PMI) is running low due to restrictions on community activities during the Covid-19 pandemic. The decline in stock was exacerbated by the public's view that the transfusion process had been contaminated with the virus. The study used Ferdinand de Saussure's semiotic analysis to examine the structure of messages on @pmikotabogor. During 2020, there were posted 896 contents. Through the categorization process, 22 relevant content (graphic) posts were obtained answering research questions, which two of them became the unit of analysis. Content as a sign was constructed through Saussure's binary opposition principal which are selection (paradigmatic axis) and combinations (syntagmatic axis). The results showed, to deal with a critical situation, PMI Bogor City conveys a “humanity call” to the public through two types of messages, namely “call for blood donors” and “safety” during blood transfusions.